A randomized clinical trial comparing guided implant surgery (bone‐ or mucosa‐supported) with mental navigation or the use of a pilot‐drill template. (10th April 2014) - Vercruyssen, Marjolein; Cox, Catherine; Coucke, Wim; Naert, Ignace; Jacobs, Reinhilde; Quirynen, Marc
Abstract Aim To assess the accuracy of guided surgery (mucosa and bone‐supported) compared to mental navigation or the use of a surgical template, in fully edentulous jaws, in a randomized controlled study. Material and Methods Fifty‐nine patients (72 jaws), requiring four to six implants (maxilla or mandible), were consecutively recruited and randomly assigned to one of the following treatment groups; guidance via Materialise Universal®/mucosa, Materialise Universal®/bone, Facilitate™/mucosa, Facilitate™/bone, or mental navigation or a pilot‐drill template. The precision was assessed by matching the planning computed tomography (CT) with a post‐operative cone beam CT. Results A significant lower mean deviation at the entry point (1.4 mm, range: 0.3–3.7), at the apex (1.6 mm, range: 0.2–3.7) and angular deviation (3.0°, range: 0.2–16°) was observed for the guiding systems when compared to mental navigation (2.7 mm, range: 0.3–8.3; 2.9 mm, range: 0.5–7.4 and 9.9°, range: 1.5–27.8) and to the surgical template group (3.0 mm, range: 0.6–6.6; 3.4 mm, range: 0.3–7.5 and 8.4°, range: 0.6–21.3°). Differences between bone and mucosa support or type of guidance were negligible. Jaw and implant location (posterior–anterior, left–right), however, had a significant influence on the accuracy when guided. Conclusion Based on these findings, guided implant placement appears to offer clear accuracy benefits.